2017
DOI: 10.15560/13.5.671
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the geographic distribution of Boana pugnax (Schmidt, 1857) (Anura, Hylidae) in Venezuela: new state records, range extension, and potential distribution

Abstract: Boana pugnax is a treefrog inhabiting open lowlands from southern Central America and northwestern South America. Its geographic distribution in Venezuela is poorly understood due, in part, its morphological similarity with B. xerophylla (with which is frequently confused) and the few localities documented. In order to increase the knowledge of the distribution of B. pugnax in the country, we examined the specimens of B. pugnax and B. xerophylla deposited in 4 Venezuelan museums, compiled the locality records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…When there was more than one final model selected, we used the median of the results of all replicates as the final model (Cobos et al, 2019). Then, we converted the continuous models obtained for each season into binary (presence vs. absence) maps using the tenth percentile training presence threshold, considering the error variation within presence records from different sources (e.g., Escalona et al, 2017). This reduced commission errors (i.e., areas of over-prediction) in our final binary maps (Liu et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…When there was more than one final model selected, we used the median of the results of all replicates as the final model (Cobos et al, 2019). Then, we converted the continuous models obtained for each season into binary (presence vs. absence) maps using the tenth percentile training presence threshold, considering the error variation within presence records from different sources (e.g., Escalona et al, 2017). This reduced commission errors (i.e., areas of over-prediction) in our final binary maps (Liu et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…This name is widely used since the species is abundant, easy to spot, present in anthropic environments, and widely distributed. Although B. platanera and B. pugnax have been misidentified in the past (La Marca 1996;Escalona et al 2017), our intention is to use the folk nomenclature as the species epithet so that it can be easily remembered by non-taxonomic experts.…”
Section: Vocalization Of Boana Xerophylla North Of the Orinoco Rivermentioning
confidence: 99%
“…According to data from the Herpetology Museum of the University of Antioquia (MHUA), approximately 30% of Colombia's amphibian species are present in this territory, represented by 230 species (~34% of Colombia's species) [16]. The nocturnal tree frog B. pugnax (Schmidt, 1857), which ranges in size from 68.9 to 77.9 mm, lives in the open lowlands of Southern Central and Northern South America [17]. Recent studies also suggested that the immune response may be incredibly efficient in frogs of the genus Boana sp., highlighting the potential of this genus in discovering new ABC peptides from the Colombian herpetofauna [18].…”
Section: Introductionmentioning
confidence: 99%